Fans, Blockbusterisation, and the Transformation of Cinematic Desire - Michelle, Carolyn. author. aut Link
XVI, 344 p. 7 illus.
Keywords: This book explores the evolution of audience receptions of Peter Jackson’s Hobbit trilogy (2012-14) as an exemplar of the contemporary blockbuster event film franchise. Drawing on findings from a unique cross-cultural and longitudinal study, the authors argue that processes and imperatives associated with Hollywood ‘blockbusterisation’ shaped the trilogy’s conditions of production, format, content, and visual aesthetic in ways that left many viewers progressively disenchanted. The chapters address public and private prefigurations of the Hobbit trilogy, modes of reception, new cinematic technologies and the Hobbit hyperreality paradox, gender representations, adaptation and the transformation of cinematic desire, and the role of social and cultural location in shaping audience engagement and response. This book will appeal to audience researchers, Q methodologists, scholars and students in film and media studies, Tolkien scholars, and Hobbit fans and critics alike.